A complicated case of myocardial infarction with nonobstructive coronary arteries with an underlying pheochromocytoma: a case report - Sodam Jung; In Sook Kang (BMC, 2022)
Abstract Background The signs and symptoms of pheochromocytoma can imitate those of many other diseases, which may result in confusion. Therefore, diagnosing and treating secondary hypertension due to pheochromocytoma in deteriorating patients becomes challenging. Case presentation A 63-year-old female patient presented to the emergency room with severe and progressive nausea. The initial diagnosis was an acute myocardial infarction based on ST-segment depression on electrocardiogram and elevated cardiac markers. Elective coronary angiography revealed nonobstructive coronary arteries. However, she suffered from a complicated clinical course for several weeks during her life-or-death crisis. She was subsequently diagnosed with a cerebral hemorrhage and a pheochromocytoma. It is unclear whether her initial presentation was due to the neurogenic stunned myocardium caused by a cerebral hemorrhage or type 2 myocardial infarction caused by a pheochromocytoma, or both. However, this case showed the significance of accurately diagnosing and treating underlying causes in patients presenting with myocardial infarction with nonobstructive coronary arteries. Early diagnosis and treatment of the pheochromocytoma may have prevented the complications experienced by the patient. Conclusions A catecholamine surge and blood pressure fluctuation caused severe complications. When a patient presents with an unusual clinical presentation, secondary hypertension due to pheochromocytoma should be suspected.